Fatores que influenciam o tratamento da osteoporose em mulheres na pós-menopausa - Montagner, Lia Mara Zamberlan (2016)
Introduction: Osteoporosis is a disorder associated with bone fragility and increased risk of fractures. It may lead to serious physical, psychosocial and economic grievances. Therefore, strategies for early diagnosis of patients at high risk for fractures have been recommended to institute treatment. Nonetheless, despite the availability of effective drugs for the prevention of bone fractures, a low adhesion to them has been observed. Objective: the aim of this study was to identify possible factors associated with the use of treatment to prevent fractures in women after menopause. Methodology: This analytical cross-sectional study was carried out from March 1 to August 31, 2013. Postmenopausal women aged over 55 who attended the Basic Health Units in the city of Santa Maria (Brazil) were included. Women with communication difficulties were excluded. All information was obtained by a standardized questionnaire. Women were considered as currently on treatment when taking one of the following drugs at the moment of the survey: alendronate, risedronate, pamidronate, zoledronic acid, raloxifene, estrogen, calcitonin, teriparatide or strontium ranelate. Past treatment was considered when the women had taken any of those drugs in the past but did not presently take it. Results: Of the 1025 subjects included, 82 (8%) were currently on treatment, 59 (5.7%) had past treatment and 884 (86.3%) never treated. Factors independently associated with treatment (current or past) were performing a bone densitometry (BMD) scan, having a diagnosis of osteoporosis by a BMD scan, and having received information about osteoporosis. Conclusion: These results suggest that properly informing patients during the consultation and the popularization of BMD scan may have a positive impact on adherence to treatment of osteoporosis and primary and secondary prevention of fractures.